Effectiveness of an add-on brief group behavioral activation treatment for depression in psychiatric care: a randomized clinical trial - Haakana, Riikka; Rosenström, Tom; Parkkinen, Lauri; Tuomisto, Martti T.; Isometsä, Erkki (Frontiers in Psychiatry, 2024)
Objective: Behavioral activation (BA) is an effective treatment for depression. We investigated the effectiveness of add-on group-format BA and peer support (PS) with treatment as usual (TAU) in a registered randomized clinical trial in psychiatric outpatient settings (ISRCTN10647845). Methods: Adult outpatients (N = 140) with major depressive disorder (MDD) and Patient Health Questionnaire (PHQ-9) score ≥ 10 were randomized into (a) group BA, consisting of eight 90-minute weekly group sessions plus TAU, (b) group PS, including eight 90-minute weekly group sessions plus TAU, or (c) TAU alone. The primary outcome was within-individual change in PHQ-9 score between baseline and eight weeks.Secondary outcomes were 1) response, 2) remission, and 3) functional impairment at eight weeks, plus 4) change in PHQ-9 at six months.Results: Of the randomized patients, 100 (71.4%) completed treatments, including 29/45 (64.4%) patients in BA, 39/49 (79.6%) in PS, and 32/46 (69.6%) in TAU groups. By eight weeks, PHQ-9 scores declined most in the TAU group (BA -0.28 [95% CI -2.48, 1.92], PS -0.58 [-2.09, 0.94] vs. TAU -3.32 [-5.21, -1.44]; groupdifferences test p = 0.034). The secondary outcomes in the BA or PS arms did not significantly differ from TAU. Videotaped sessions revealed marked variation in briefly trained therapists' adherence to the treatment manual.Conclusions: In this randomized trial, the effectiveness of treatments with the added BA and PS groups did not exceed TAU alone. The preconditions in which brief BA or PS group interventions benefit outpatients with depression in psychiatric settings warrant critical investigation.